THE ROLE OF MUSLIM TOURISTS’ ECOTHEOLOGICAL AWARENESS IN SHAPING PREFERENCES AND NATURE-BASED TOURISM BEHAVIOR IN PEKALONGAN - Adinugraha, Hendri Hermawan; M. Sugeng Solehuddin; Moh. Nasrudin (Islamic Studies Journal for Social Transformation, 2025)
Nature-based tourism in Pekalongan has shown rapid growth as Muslim tourists’ awareness of the importance of environmental sustainability as part of Islamic values increases. This study aims to analyze the role of ecotheological awareness in shaping the preferences and behavior of Muslim tourists towards nature-based tourism destinations. Using a qualitative approach, this study explores the relationship between theological understandings of the concepts of caliphate, trust, and tawhid and destination selection patterns, as well as responsible tourism behavior, through a literature review and descriptive survey data from 120 respondents. The results show that Muslim tourists with high levels of ecotheological awareness tend to choose destinations that are sustainable, tranquil, and provide spiritual value. They also demonstrate ethical tourism behavior, such as refraining from damaging nature, bringing their trash bags, and participating in conservation programs. The correlation between ecotheological awareness and tourism preferences was significant, with an r-value of 0.512, while the correlation with tourism behavior reached an r-value of 0.643. This study concludes that ecotheological awareness plays a vital role in promoting more sustainable, value-based tourism. These findings provide a conceptual basis for developing a nature tourism model that is not only environmentally friendly but also spiritually nuanced, while encouraging tourism policies that integrate Islamic and ecological values.